Studi Literatur: Faktor-Faktor yang Mempengaruhi Nilai Perusahaan - Eka Erllyana (LPPM Universitas Putera Batam, 2026)
Firm value is a crucial aspect in financial management research as it reflects the ability of a company to generate profits and maximize shareholder welfare. This study uses a literature review approach to examine factors influencing firm value, specifically profitability measured by Return on Equity (ROE), leverage measured by Debt to Equity Ratio (DER), and firm size (natural logarithm of total assets) as a moderating variable, with Price to Book Value (PBV) as the proxy for firm value. The theoretical foundation is grounded in agency theory (Jensen & Meckling, 1976) and signaling theory. The review of relevant studies indicates that profitability has a significant positive effect on firm value, while the effect of leverage tends to be inconsistent across studies. Firm size is evidenced to strengthen or weaken the relationship between independent variables and firm value. These findings provide important insights for investors and managers in the consumer non-cyclical sector listed on the Indonesia Stock Exchange (IDX). Keywords: Firm Value, Profitability, Leverage, Firm Size, PBV, ROE, DER